Elastase Activity in Aspergillus fumigatus Can Arise by Random, Spontaneous Mutations. (11th April 2010) - Álvarez-Pérez, Sergio; Blanco, Jose L.; López-Rodas, Victoria; Flores-Moya, Antonio; Costas, Eduardo; García, Marta E.
Abstract : Aspergillus fumigatus Fresenius has the capacity to degrade elastin (the principal protein of the lungs) and it is considered that elastase activity (EA) is among the most important pathogenicity factors of this mold. In particular, there is a strong correlation between EA in A. fumigatus and invasive aspergillosis. However, EA is not universal in this mold, and it is unknown whether the capacity to degrade elastin is the consequence of physiological mechanisms and/or genetic changes (putative adaptive mutations) induced after the exposure to this substrate or, on the contrary, it is due to random spontaneous mutations that occur under nonselective conditions. In order to discriminate between these possibilities, a Luria-Delbrück fluctuation analysis was carried out on an elastase-negative (EA − ) A. fumigatus strain, using as selective factor a culture medium containing elastin as the sole source of nitrogen. Here we show that theEA − → EA + transformation in A. fumigatus appears by rare, random mutations before the exposure of the strain to selective conditions. This work represents the first experimental evidence of pathogenicity factor acquisition in mycelial fungi by preselective mutation.